Update on integrative treatment of psychiatric symptoms and disorders in athletes - Glick, I. D.; Stillman, M. A.; McDuff, D. (The Physician and Sportsmedicine, 2020)
Primary objective: In this review, we detail the issues and disorders athletes present with, guidelines for making diagnostic formulations and treatment goals, and strategies for delivering integrated treatment attuned to the athlete and their team and/or sport. In addition, we highlight special issues associated with athletes and their families.